2007
DOI: 10.1093/jac/dkm058
|View full text |Cite
|
Sign up to set email alerts
|

AdeABC multidrug efflux pump is associated with decreased susceptibility to tigecycline in Acinetobacter calcoaceticus–Acinetobacter baumannii complex

Abstract: Objectives: To investigate the role of the AdeABC multidrug efflux pump in the decreased susceptibility of clinical isolates of Acinetobacter calcoaceticus-Acinetobacter baumannii complex to tigecycline.Methods: Gene expression was analysed by Taqman RT-PCR. A single cross-over achieved insertional inactivation of the adeB gene with a suicide plasmid construct carrying an adeB fragment obtained by PCR. Analysis of the adeRS locus was performed by PCR and sequencing. Ribotyping was performed with the RiboPrinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(193 citation statements)
references
References 12 publications
11
177
2
2
Order By: Relevance
“…This finding is consistent with Buckley et al (2006), where the authors reported a similar antibiotic-susceptibility trend for acrB and tolC knockouts in Salmonella enterica, and with Ruzin et al (2007), where the same finding was reported for an adeB knockout strain (inner-membrane transporter of the AdeABC multidrug efflux pump homologous to AcrAB of E. coli). Hypersusceptibility to a variety of compounds was also reported for acrAB deletion mutants in E. coli (Ma et al, 1995); AcrAB is a pump to which S. marcescens SdeAB is closely related.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with Buckley et al (2006), where the authors reported a similar antibiotic-susceptibility trend for acrB and tolC knockouts in Salmonella enterica, and with Ruzin et al (2007), where the same finding was reported for an adeB knockout strain (inner-membrane transporter of the AdeABC multidrug efflux pump homologous to AcrAB of E. coli). Hypersusceptibility to a variety of compounds was also reported for acrAB deletion mutants in E. coli (Ma et al, 1995); AcrAB is a pump to which S. marcescens SdeAB is closely related.…”
Section: Discussionsupporting
confidence: 89%
“…This system was shown to be responsible for decreased susceptibility to a broad spectrum of antimicrobials. Aminoglicosides, tetracyclines, erythromycin, chloramphenicol, trimethoprim, fluoroquinolones, some β-lactams, ethidium bromide [30,37,73,135], and also recently tigecycline [92,110], were found to be substrates for AdeABC, although netilmicin and gentamicin appeared to be the best one for the pump [73].…”
Section: The Structure Of Rnd-family Efflux Pumpsmentioning
confidence: 99%
“…Experiment performed by Ruzin et al [110] suggests, that AdeABC MDR efflux pump decreased susceptibility to tigecycline -the first member of a new class of modified tetracycline antimicrobials known as glycylcyclines. In this study the adeB gene was disrupted by insertional inactivation using a suicide plasmid in two derivative mutants constructed from two clinical isolates.…”
Section: Level Of Expressionmentioning
confidence: 99%
“…Tigecycline is the first commercially available member of the glycylcyclines, and multidrug-resistant strains of A. baumannii often retain susceptibility to tigecycline. Known mechanisms of resistance to tigecycline mainly involve active efflux by AdeABC, AdeIJK, and AdeFGH (35,44). Several worldwide reports indicate an increasing trend of resistance to tigecycline in isolates of A. baumannii (40).…”
Section: Genetic Basis Of Resistance To Cyclinesmentioning
confidence: 99%